2019
DOI: 10.15252/embr.201847202
|View full text |Cite
|
Sign up to set email alerts
|

Tau accumulation triggers STAT 1‐dependent memory deficits by suppressing NMDA receptor expression

Abstract: Intracellular tau accumulation forming neurofibrillary tangles is hallmark pathology of Alzheimer's disease (AD), but how tau accumulation induces synapse impairment is elusive. By overexpressing human full‐length wild‐type tau (termed hTau) to mimic tau abnormality as seen in the brain of sporadic AD patients, we find that hTau accumulation activates JAK2 to phosphorylate STAT1 (signal transducer and activator of transcription 1) at Tyr701 leading to STAT1 dimerization, nuclear translocation, and its activati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 54 publications
10
54
0
Order By: Relevance
“…Our previous paper reported that hTau accumulation activated tyrosine kinase JAK2, JNK and ERK, which are reported to mediate phosphorylation of the STAT family [24]. Here, we also found that P301L-hTau activated JAK2, JNK and ERK (Additional le 1: Figure S9a, b).…”
Section: Jak2 Kinase Mediates Phosphorylation Of Stat3 At Y705supporting
confidence: 79%
See 2 more Smart Citations
“…Our previous paper reported that hTau accumulation activated tyrosine kinase JAK2, JNK and ERK, which are reported to mediate phosphorylation of the STAT family [24]. Here, we also found that P301L-hTau activated JAK2, JNK and ERK (Additional le 1: Figure S9a, b).…”
Section: Jak2 Kinase Mediates Phosphorylation Of Stat3 At Y705supporting
confidence: 79%
“…Intracellular P301L-hTau accumulation inactivates STAT3 despite the level of phosphorylated STAT3 increases In our previous study, we found that the accumulated htau increased STAT1 activity, while the activity of HNF1, HOX4C, PLAG1, SMUC, VDR, SF-1 and PIT1 decreased remarkably [24]. STAT3 and STAT1 belong to the STAT protein family, and both are reported to be involved in cognitive functions [25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Given that many kinases can be activated by Ca 2+ , dysregulation of Ca 2+ homeostasis, such as seen during ER stress, can increase tau phosphorylation [14,72,73]. Conversely, intracellular tau accumulating can also induce ER stress and cause Ca 2+ overload, the latter induces dephosphorylation of Ca 2+ -calmodulin-dependent protein kinase IV (CaMKIV) and cAMP-responsive element binding protein (CREB) by activating calcineurin [5]; the Ca 2+ overload can also activate JAK2-STAT1 signaling, and the upregulated STAT1 directly binds to the specific GAS elements of N-methyl-D-aspartate receptors (NMDARs) and thus inhibits the transcription of NMDARs [14]; the cleaved tau-induced STAT1 elevation also activates BACE1 to promote Aβ production [74]; all of which reveal new mechanisms underlying tau-induced synapse impairments and cognitive deficits.…”
Section: Calciummentioning
confidence: 99%
“…[5][6][7]. Recent studies suggest that tau hyperphosphorylation may play a dual role in AD neurodegeneration, i.e., tau hyperphosphorylation renders the cells more resistant to acute apoptosis [8][9][10][11][12], while the increasing intracellular tau accumulation induces multiple cellular impairments, including endoplasmic reticulum (ER) stress, deficits of mitophagy and autophagy, deficits of synaptic transmission, etc., and eventually leads to a chronic neurodegeneration [5,13,14].…”
Section: Introductionmentioning
confidence: 99%